Characteristics and distribution of continental tight oil in China. (July 2019) - Zhu, Rukai; Zou, Caineng; Mao, Zhiguo; Yang, Haibo; Hui, Xiao; Wu, Songtao; Cui, Jingwei; Su, Ling; Li, Sen; Yang, Zhi
Highlights: Multipel controlling factors of organic matter accumulation are summrarized. Characteristics of tight reservoir are discribled in by multiple-scale approaches. Based on the case study on Junngar basin, the tight oil "sweet pot" is evaluated. Abstract: Tight oil in China is mainly distributed in Mesozoic-Cenozoic continental petroliferous basins, either generally occurs in tight sandstone or tight carbonate reservoirs which are paragenetic to or in contact with lacustrine petroleum source rocks. By the end of 2016, the continental tight oil in China has established an annual production capacity of 1.55 million tons, and a cumulative oil production of 2.52 million tons. In 2016, the continental tight oil production in China was about 800, 000 tons. By analyzing the characterization of the tight oil in Ordos Basin, Songliao Basin, Jungar Basin, the organic-rich shale in China were formed in multiple geological periods including the Permian, Triassic, Jurassic, Cretaceous, Neogene, and Paleogene, in freshwater, semi-saline to hyper-saline lacustrine depositional setting. They are generally tens of meters to several hundreds of meters thick, have total organic carbon (TOC) contents of 0.4–16%, and thermal maturity of 0.4–1.4%. Algal bloom as results of volcanism, low sedimentation rate, transgression, and stratification of water body are prominent factors controlling the formation of organic-rich shales. Tight oil reservoirs in China mainly include tight sandstone, tight carbonate rock, tight sedimentary tuff, etc., all of which are characterized by strong heterogeneity and poor petrophysical properties, with in situ porosity and permeability generally no more 12% and 1 × 10 −3  μm 2 respectively. They are also characterized by tight pore-throat systems of nano- to micro-scales, with pore throat diameters in the range of 80–1800 nm, and complex pore structures. The producing reservoirs have pressure coefficients between 0.7 and 1.8, covering under-pressure to over-pressure. Crude oil properties vary greatly with densities ranging from 0.75 to 0.92 g/cm 3 . It is believed that the abundance and effectiveness of hydrocarbon supply controls the formation of oil saturation, and tight oil "sweet spots" are generally in or near the areas with high hydrocarbon expulsion intensities. In addition, the quality of the source rock and the type of source reservoir control the distribution of the "sweet spots", and storage space and movable fluid guarantee the formation of the "sweet spot" area of high oil saturation. "Sweet spots" are often developed in local mini-structural highs under a broad and gentle-sloped background. Continental tight oil in China has estimated geological resource of 14.66 × 10 9  tons with a technically recoverable resource of 1.45 × 10 9  tons. Tight oil is mainly distributed in Ordos Basin, Songliao Basin, Bohai Bay Basin, Junggar Basin, and Qaidam Basin, within the Mesozoic and Cenozoic formations. Overall China has a relatively large tight oil reserve and good exploration prospect.